Potencialidades das narrativas para a formação inicial de professores que ensinam matemática - Flugge, Flávia Cristina Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The main aim of this study is to produce an understanding of the possibilities and limitations of narratives and of oral history as part of a problematising teaching approach, within Pedagogy courses focusing on mathematics and its teaching. The study is part of the project Oral history as a resource on the development of pre- and in-service teacher education, led by the supervisor of the present study. We have followed the discipline Content, methods and practice of mathematics teaching, in the year 2013, as part of a Pedagogy course at UNESP/Rio Claro. We proposed material involved with mathematics and its teaching, using strategies consistent with the interest of the broader project. Oral history was used as the research methodology. We analyzed the narratives produced by the teacher-students and the narrative produced from an interview with some of the teacher-students. We assess the approach proposed through the strategies adopted, based on narratives and oral history as tools for enhancing the education and professional development of future teachers of mathematics. This approach enabled the reflection and discussion of the participants through their experiences about memories and experiences as students, about the perception they have of themselves regarding mathematics and its teaching besides other experiences through written and oral narratives and through teachers on issues related to mathematics during the course and teacher practices. This activity resulted in a coherence perspective regarding future performances as professionals who teach mathematics. We evaluate the narrative approach and the use of HO as a fruitful tool in order to stimulate formative processes of educators who will work in the mathematics area

Tecer uma compreensão sobre as possibilidades, limitações e potencialidades das narrativas e da História Oral como integradoras de uma abordagem de ensino de caráter problematizador em disciplinas de cursos de Pedagogia que discutam a Matemática e seu ensino é o objetivo principal desta pesquisa. Ela se insere em um projeto intitulado A História Oral como Recurso no Desenvolvimento da Formação Inicial e Continuada de Professores de Matemática, idealizado e coordenado pela orientadora deste trabalho, cujo objetivo é elaborar, aplicar e analisar estratégias de formação de professores de Matemática ou que ensinam matemática em cursos de Licenciatura em Matemática, de Pedagogia e Extensão, de modo que a História Oral e as narrativas estejam presentes de forma relevante. Nossa participação se deu por meio do acompanhamento, durante o ano de 2013, da disciplina Conteúdo, Metodologia e Prática do Ensino da Matemática do curso de Pedagogia da Unesp/Rio Claro. Nela, foram propostas atividades elaboradas a partir dos interesses do projeto, com cuja parte este trabalho colabora. A metodologia de pesquisa qualitativa utilizada foi a da História Oral. Compreendemos que essa metodologia, por meio de seus procedimentos, para o registro de narrativas e sua análise inicial,deu-se em um processo de conhecimento e reconhecimento das estratégias que foram aplicadas e investigadas. A análise das narrativas produzidas pelos estudantes a partir das atividades e da narrativa constituída por intermédio da entrevista realizada com alguns deles teve como foco as discussões e envolvimentos promovidos pela abordagem narrativa na referida disciplina. Tal abordagem possibilitou a reflexão e discussão das colaboradoras por meio de suas memórias sobre experiências/vivências enquanto alunas, sobre a visão que têm de si em relação à matemática e seu ensino e de outras vivências por meio do contato de narrativas escritas e orais...
Keywords: Teachers, Training of; Professores - Formação; Matemática - Estudo e ensino; Historia oral; Educação